Oleanolic acid induces mitochondrial-dependent apoptosis and G0/G1 phase arrest in gallbladder cancer cells - Li HF; Wang XA; Xiang SS; Hu YP; Jiang L; Shu YJ; Li ML; Wu XS; Zhang F; Ye YY; Weng H; Bao RF; et al. (Dove Medical Press, 2015)
Huai-Feng Li,1–3,* Xu-An Wang,1–3,* Shan-Shan Xiang,1–3,* Yun-Ping Hu,1–3 Lin Jiang,1–3 Yi-Jun Shu,1–3 Mao-Lan Li,1–3 Xiang-Song Wu,1–3 Fei Zhang,1–3 Yuan-Yuan Ye,1–3 Hao Weng,1–3 Run-Fa Bao,1–3 Yang Cao,1–3 Wei Lu,1–3 Qian Dong,1–3 Ying-Bin Liu1–3 1Department of General Surgery, 2Laboratory of General Surgery, 3Institute of Biliary Tract Disease, Xinhua Hospital, Affiliated to Shanghai Jiao Tong University, School of Medicine, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Oleanolic acid (OA), a naturally occurring triterpenoid, exhibits potential antitumor activity in many tumor cell lines. Gallbladder carcinoma is the most common malignancy of the biliary tract, and is a highly aggressive tumor with an extremely poor prognosis. Unfortunately, the effects of OA on gallbladder carcinoma are unknown. In this study, we investigated the effects of OA on gallbladder cancer cells and the underlying mechanism. The results showed that OA inhibits proliferation of gallbladder cancer cells in a dose-dependent and time-dependent manner on MTT and colony formation assay. A flow cytometry assay revealed apoptosis and G0/G1 phase arrest in GBC-SD and NOZ cells. Western blot analysis and a mitochondrial membrane potential assay demonstrated that OA functions through the mitochondrial apoptosis pathway. Moreover, this drug inhibited tumor growth in nude mice carrying subcutaneous NOZ tumor xenografts. These data suggest that OA inhibits proliferation of gallbladder cancer cells by regulating apoptosis and the cell cycle process. Thus, OA may be a promising drug for adjuvant chemotherapy in gallbladder carcinoma. Keywords: oleanolic acid, gallbladder carcinoma, apoptosis, cell cycle arrest, mitochondrial pathway